Tìm x:
\(|4+2x|=-4x\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
`2//(5x-8)-3(4x-5)=4(3x-4)`
`<=>5x-8-12x+15=12x-16`
`<=>-19x=-23`
`<=>x=23/19` Vậy `x=23/19`
`3//2(x^3-1)-2x^2(x+2x^4)+(4x^5+4)x=6`
`<=>2x^3-2-2x^3-4x^6+4x^6+4x=6`
`<=>4x=8`
`<=>x=2` Vậy `x=2`
a: Ta có: \(\left(8x^2-4x\right):\left(-4x\right)-\left(x+2\right)=8\)
\(\Leftrightarrow-2x+1-x-2=8\)
\(\Leftrightarrow-3x=9\)
hay x=-3
b: Ta có: \(\left(2x^4-3x^3+x^2\right):\left(-\dfrac{1}{2}x^2\right)+4\left(x-1\right)^2=0\)
\(\Leftrightarrow-4x^2+6x-2+4x^2-8x+4=0\)
\(\Leftrightarrow-2x=-2\)
hay x=1
`C(x)=`\(5-8x^4+2x^3+x+5x^4+x^2-4x^3\)
`C(x)= (-8x^4+5x^4)+(2x^3-4x^3)+x^2+x+5`
`C(x)= -3x^4-2x^3+x^2+x+5`
`D(x)=`\(\left(3x^5+x^4-4x\right)-\left(4x^3-7+2x^4+3x^5\right)\)
`D(x)= 3x^5+x^4-4x-4x^3+7-2x^4-3x^5`
`D(x)=(3x^5-3x^5)+(x^4-2x^4)-4x^3-4x+7`
`D(x)=-x^4-4x^3-4x+7`
`P(x)=C(x)+D(x)`
`P(x)=( -3x^4-2x^3+x^2+x+5)+(-x^4-4x^3-4x+7)`
`P(x)=-3x^4-2x^3+x^2+x+5-x^4-4x^3-4x+7`
`P(x)=(-3x^4-x^4)+(-2x^3-4x^3)+x^2+(x-4x)+(5+7)`
`P(x)=-4x^4-6x^3+x^2-3x+12`
`Q(x)=C(x)-D(x)`
`Q(x)=( -3x^4-2x^3+x^2+x+5)-(-x^4-4x^3-4x+7)`
`Q(x)=-3x^4-2x^3+x^2+x+5+x^4+4x^3+4x-7`
`Q(x)=(-3x^4+x^4)+(-2x^3+4x^3)+x^2+(x+4x)+(5-7)`
`Q(x)=-2x^4+2x^3+x^2+5x-2`
`F(x)=Q(x)-(-2x^4+2x^3+x^2-12)`
`F(x)=(-2x^4+2x^3+x^2+5x-2)-(-2x^4+2x^3+x^2-12)`
`F(x)=-2x^4+2x^3+x^2+5x-2+2x^4-2x^3-x^2+12`
`F(x)=(-2x^4+2x^4)+(2x^3-2x^3)+(x^2-x^2)+5x+(-2+12)`
`F(x)=5x+10`
Đặt `5x+10=0`
`\Leftrightarrow 5x=0-10`
`\Leftrightarrow 5x=-10`
`\Leftrightarrow x=-10 \div 5`
`\Leftrightarrow x=-2`
Vậy, nghiệm của đa thức là `x=-2.`
1: Ta có: \(\left(x+3\right)^2-\left(x+2\right)\left(x-2\right)=4x+17\)
\(\Leftrightarrow x^2+6x+9-x^2+4-4x=17\)
\(\Leftrightarrow x=2\)
3: Ta có: \(\left(2x+3\right)\left(x-1\right)+\left(2x-3\right)\left(1-x\right)=0\)
\(\Leftrightarrow2x^2-2x+3x-3+2x-2x^2-3+3x=0\)
\(\Leftrightarrow6x=6\)
hay x=1
a: \(P=\left(\dfrac{3}{2\left(x+2\right)}-\dfrac{x}{x-2}+\dfrac{2x^2+3}{\left(x-2\right)\left(x+2\right)}\right)\cdot\dfrac{4\left(x-2\right)}{2x-1}\)
\(=\left(\dfrac{3\left(x-2\right)}{2\left(x+2\right)\left(x-2\right)}-\dfrac{2x\left(x+2\right)}{2\left(x-2\right)\left(x+2\right)}+\dfrac{4x^2+6}{2\left(x-2\right)\left(x+2\right)}\right)\cdot\dfrac{4\left(x-2\right)}{2x-1}\)
\(=\dfrac{3x-6-2x^2-4x+4x^2+6}{2\left(x+2\right)\left(x-2\right)}\cdot\dfrac{4\left(x-2\right)}{2x-1}\)
\(=\dfrac{2x^2-x}{x+2}\cdot\dfrac{2}{2x-1}=\dfrac{2x}{x+2}\)
b: Khi 4x2-1=0 thì (2x-1)(2x+1)=0
=>x=1/2(loại) và x=-1/2(nhận)
Khi x=-1/2 thì \(P=\left(2\cdot\dfrac{-1}{2}\right):\left(-\dfrac{1}{2}+2\right)=-1:\dfrac{3}{2}=-\dfrac{2}{3}\)
Với `x \ne +-2,x \ne 1/2,x \ne0`. Ta có:
`(3/[2x+4]+x/[2-x]+[2x^2+3]/[x^2-4]):[2x-1]/[4x-8]`
`=(3/[2(x+2)]-x/[x-2]+[2x^2+3]/[(x-2)(x+2)]).[4(x-2)]/[2x-1]`
`=[3(x-2)-2x(x+2)+2(2x^2+3)]/[x(x-2)(x+2)].[4(x-2)]/[2x-1]`
`=[3x-6-2x^2-4x+4x^2+6]/[x(x+2)]. 4/[2x-1]`
`=[2x^2-x]/[x(x+2)]. 4/[2x-1]`
`=[x(2x-1)]/[x(x+2)] . 4/[2x-1]`
`=4/[x+2]`
Ta có : |4 + 2x| = - 4x
=> - 4x \(\ge\) 0
=> -x \(\ge\)0
=> x \(\le\)0
\(\orbr{\begin{cases}4+2x=4x\\4+2x=-4x\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}4x-2x=4\\4x+2x=-4\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}2x=4\\6x=-4\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=2\left(\text{loại}\right)\\x=-\frac{2}{3}\left(\text{TM}\right)\end{cases}}\)
Vậy \(x=-\frac{2}{3}\)
|4 + 2x| = -4x
4 + 2x = -4x hoặc -(4 + 2x) = -4x
4 = -4x - 2x -4 - 2x = -4x
4 = -6x -4 = -4x + 2x
-2/3 = x -4 = -2x
x = -2/3 2 = x
x = 2